Investigating dialectal variation in the English of Nigerian university graduates: Methodology and pilot study - Akande, Akinmade Timothy (Adam Mickiewicz University, 2008)
This paper describes the methodological procedures that will be used in the collection of data for a dialectal study of the English of Nigerian university graduates. It also reports on a pilot study carried out on this topic. The major elicitation instrument will be a Labovian sociolinguistic interview which will be supplemented by reading materials (Labov 1966). The study will also draw heavily on the current SuRE methodology by Upton and Llamas (1999). The theoretical framework that will be used in the analysis of data will be a diglossia model as this approach enables one to view Nigerian English (NE) and Nigerian Pidgin English (NPE) as two languages operating in an extended diglossic situation.